"Dead Souls" and "Open Vessel." Is There a Need for a "New" Meaning of the Hebrew Word nefeš? - Lemański, Janusz (Verbum Vitae, 2022)
The noun nefeš is ascribed the sense of “corpse” in several instances of the Hebrew Bible. All of them are analysed to trace the possible development of the semantic field of this word. It leads to the conclusion that this implied sense arose from the shortening of longer phrases (nefeš ’ādām; nefeš mēt). The noun nefeš used in them, however, retains its basic meaning of “person,” and its reference to a corpse is only apparent from the context. In a similar sense, the author also reads the use of the abbreviated version, which represents a person and not just a corpse (synecdoche) – a person who dies and gradually passes into the hereafter.